2000
DOI: 10.1007/s004390000389
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human nebulette gene: a polymorphism in an actin-binding motif is associated with nonfamilial idiopathic dilated cardiomyopathy

Abstract: Idiopathic dilated cardiomyopathy (IDC) is characterized by a thin-walled heart with systolic dysfunction of unknown etiology. Because abnormalities in genes for cytoskeletal proteins related to Z-disc function have recently been reported to cause IDC, genomic organization of the gene for nebulette, a novel actin-binding Z-disc protein, was determined and its sequence variations were searched for in Japanese patients with IDC and healthy controls. The nebulette gene consists of 28 exons, and four sequence vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 54 publications
0
35
0
Order By: Relevance
“…This gene spanned 390 kb and encompassed seven exons. Surprisingly, the last three exons of the novel gene were found to be identical to three exons from the 3Ј part of the human gene for the cytoskeletal protein nebulette (27). We therefore concluded that the novel protein must represent a splice variant of human nebulette.…”
Section: Identification Of Human and Mouse Lim-nebulette-exten-mentioning
confidence: 80%
See 1 more Smart Citation
“…This gene spanned 390 kb and encompassed seven exons. Surprisingly, the last three exons of the novel gene were found to be identical to three exons from the 3Ј part of the human gene for the cytoskeletal protein nebulette (27). We therefore concluded that the novel protein must represent a splice variant of human nebulette.…”
Section: Identification Of Human and Mouse Lim-nebulette-exten-mentioning
confidence: 80%
“…Furthermore, defects in the nebulette gene are associated with the nonfamilial form of idiopathic dilated cardiomyopathy, which is characterized by a thinwalled heart (27). We have argued that LIM-nebulette might play a role in the assembly of focal adhesions similar to the role played by nebulin and nebulette in the assembly of the sarcomeric Z-disks.…”
Section: Fig 4 Interaction Of Zyxin With Lasp-1 As Demonstrated By mentioning
confidence: 98%
“…As a number of missense mutations in genes encoding for titin and titin-associated proteins have recently been reported to be responsible for DCM, 3,[12][13][14][15][19][20][21][22][23][24][25] we searched in a well-characterized sample of DCM patients for unknown SNPs and/or mutations in the human MYPN and ANKRD1 genes. In order to extend our knowledge on disease-causing mutations in these two proteins expressed in heart tissue, we screened the coding sequences and corresponding intron flanks of the two genes and found two novel non-synonymous mutations in the MYPN gene and only one rare synonymous SNP in the coding region of the ANKRD1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…63 More recently, 4 heterozygous missense mutations (K60N, Q128R, G202R, A592E) with different locations within the nebl gene were identified in patients with DCM and absent from 300 ethnically matched control subjects. 64 The 4 variants are all localized in the nebulin repeat region with the K60N, Q128R, G202R, and A592E variants residing in nebulin repeats 1, 3, 5, and 16, respectively (Figure).…”
Section: Nebulettementioning
confidence: 99%